Methylated arginines and nitric oxide in end-stage renal disease: impact of inflammation, oxidative stress and haemodialysis. (14th May 2013) - Bouteldja, Nadia; Woodman, Richard J.; Hewitson, Chris L.; Domingo, Enric; Barbara, Jeffrey A.; Mangoni, Arduino A.
Abstract: Objectives : To determine whether inflammation (C-reactive protein, CRP), oxidative stress (malondialdehyde, MDA) or haemodialysis (HD) affect associations between asymmetric (ADMA), symmetric (SDMA) dimethylarginine, NG-monomethyl-L-arginine (L-NMMA) and nitrite/nitrate (NOx) in end-stage renal disease (ESRD). Method : Metabolites were measured pre-HD, after 1 hour and end-HD in 40 ESRD patients (age 63 ± 14 years). Results : Positive associations between NOx and ADMA ( p  = 0.04), SDMA ( p  < 0.001) and L-NMMA ( p  = 0.04) were observed pre-HD. Associations weakened during HD but were not significantly influenced by CRP or MDA. Conclusions : HD, oxidative stress or inflammation did not significantly affect the positive associations between methylated arginines and NOx in ESRD.